PROCESSOS ALTERNATIVOS DE TRATAMENTO DE SUPERFÍCIES METÁLICAS À BASE DE NANOCERÂMICAS - Oliveira, Marilei de Ftima (2013)
The phosphate is currently the most widely used technique for the treatment of carbon steel, surface preparation for receiving ink. This process employs a solution of phosphoric acid and zinc and nickel salts for forming a crystalline phosphate layer on the metal surface. The use of metal ions with allergenic and toxic properties, for example, nickel, and generate solid waste with high content of phosphate, prevents the industries that use these conventional treatments to meet environmental regulations. The main objective of this work is to develop alternative surface treatment of 1008 carbon steel. Techniques employed were: measures open circuit potential, anodic polarization, electrochemical impedance spectroscopy, optical microscopy and scanning electron microscopy, energy dispersive spectroscopy and Raman, corrosion tests in saline chamber and chemometrics. The process of forming a protective layer on the basis of ions zirconila (ZrO2+) to protect the carbon steel was developed without the use of elevated temperatures or any significant modification of conventional processes for surface treatment such as phosphating. In this context two molecules were tested Self Assembled Monolayer-SAM, designated SAM 1 and SAM 2, to serve as a bridge between the metal surface and the ions zirconium. The best conditions for deposition of these molecules were obtained by chemometric method. The results of electrochemical measurements and microscopy showed that processes SAM 1 +Zr and SAM 2 +Zr are better than treatments phosphates. The results of accelerated corrosion in NaCl 0.5 mol / L conducted over a 500 hour period suggested that the SAM film formed and SAM 1 + Zr and SAM ²+ Zr, provides great adherence of the metallic ink to the substrate, minimizing or even inhibiting the occurrence corrosion. Another layer tested was the base SAM1 + Zr + Ti, which demonstrated less protection in relation to electrochemical tests, but showed good resistance to accelerated corrosion.